DAMPAK PELATIHAN KETERAMPILAN HIDUP (LIFE SKILLS) MONTIR OTOMOTIF TERHADAP KESEMPATAN KERJA DAN PENDAPATAN WARGA BELAJAR - Dayat Hidayat (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2016)
The purpose of this study was to analyze the implementation of life skills for automotive mechanic in CLC Cepat Tepat, which includes the steps of planning, implementation and assessment to improve employment and learners income. The approach used in this study is qualitative case study method. The data collection techniques through observation, interviews and documentation study. Subjects are six people consisting of four learners, one of organizer, and one of learning resources or trainers. Analysis of data used an interactive model, through the following steps: collection of data, reduction of data, display of data, and conclusion or verification. The results showed that the implementation of life skills training for automotive mechanic started by the analysis of learning needs of learners and carrying capacity which available in the CLC. Life skill training program for automotive mechanic is going well by involving all components of life skills. The results showed that the implementation of life skill training are skill enhancing in the areas of automotive and entrepreneurial attitudes of learners independently. The impact of life skills training program showed an increasing of getting chance to have job and learners’ income to open his own workshop or others automotive ones and automotive industry companies in Karawang.